Antibiotic treatment for patients with amniotic fluid "sludge" to prevent spontaneous preterm birth: A historically controlled observational study. (1st April 2019) - Hatanaka, Alan Roberto; Franca, Marcelo Santucci; Hamamoto, Tatiana Emy Nishimoto Kawanami; Rolo, Liliam Cristine; Mattar, Rosiane; Moron, Antonio Fernandes
Abstract: Introduction: Amniotic fluid "sludge" has been associated with an increased rate of spontaneous preterm delivery before 35 weeks, a higher frequency of clinical and histologic chorioamnionitis in a high‐risk population. Only one study evaluating the use of antibiotics in the presence of amniotic fluid "sludge" showed reduced rates of spontaneous preterm birth at <34 weeks. The objective of this study was to evaluate routine antibiotic treatment in the presence of amniotic fluid "sludge" for prevention of preterm delivery. Material and methods: A historically controlled observational study was performed between October 2010 and January 2015, including a total of 86 pregnant women with singleton pregnancies and the presence of amniotic fluid "sludge" at ultrasound. Women admitted from October 2010 to September 2012 received no treatment with antibiotics, whereas those admitted from October 2012 to January 2015, received routinely clindamycin and first‐generation cephalosporin. The groups were compared considering the incidence of spontaneous preterm delivery. The effect of antimicrobials was also compared in the subgroup of women at high risk for spontaneous preterm birth (ie, cervical length ≤25 mm, history of spontaneous preterm birth, previous spontaneous loss in the second trimester, Mullerian malformations or cervical conization). Results: Antibiotic therapy reduced the incidence of spontaneous preterm birth at <34 weeks (13.2% vs 38.5%, P  =   0.047) in women at high‐risk for preterm birth, with an odds ratio of 0.24 (95% confidence interval [CI] 0.06‐0.99). Birthweight was significantly different between the study groups (2961 ± 705 vs. 2554 ± 819 g, respectively; P  =   0.028), with no statistical significance for others variables. Conclusions: This study suggests that antibiotic treatment in high‐risk pregnant women with amniotic fluid "sludge" can be effective in the reduction of the frequency of spontaneous preterm delivery and can increase the birthweight.